Dental stem cells the magical cells - current application and the future with review of literature - Ahtesham Ahmad; Rafi Ahmad Togoo; Nilofar Nawab Jamadar (Al Ameen Medical College, 2018)
With increase in the understanding of stem-cell behavior, their application has extended well beyond not only regenerative medicine but also dentistry. The breakthrough of stem cells has produced new possibilities in the regeneration of different organs and tissues. In past few years many studies and revelations have been conducted in dentistry which indicate that stem cells and tissue engineering together are a unit have given rise to so called "Regenerative Dentistry". The tooth (permanent teeth and deciduous teeth) is the natural store house for these stem cells. These are capable of reproducing themselves and can be voluntarily recovered at the time of an intended dental procedure. Besides dental stem cells have lot of medical benefits in the progress of new medical therapies. Like regenerative diseases and cancer therapy. This article highlights the research in dental field on Stem cells their current applications and what can be done and achieved in the future.